Organic resource quality influences short-term aggregate dynamics and soil organic carbon and nitrogen accumulation - Chivenge, Pauline P.; Vanlauwe, Bernard; Gentile, R; Six, Johan (Elsevier, 2011)
Organic C inputs and their rate of stabilization influence C sequestration and nutrient cycling in soils. This study was undertaken to explore the influence of the combined application of different quality organic resources (ORs) with N fertilizers on the link between aggregate dynamics and soil organic C (SOC) and soil N. A mesocosm experiment was conducted in Embu, central Kenya where 4 Mg C ha?1 of Tithonia diversifolia (high quality), Calliandra calothyrsus (intermediate quality) and Zea mays (maize; low quality) were applied to soil compared to a no-input control. Each treatment was fertilized with 120 kg N ha?1 as urea [(NH2)2CO] or not fertilized. The soils used in the mesocosms were obtained from a three-year old-field experiment in which the same treatments as in the mesocosm were applied annually. No crops were grown in both the mesocosms and the thee-year field experiment. Soil samples were collected at zero, two, five and eight months after installation of the mesocosms and separated into four aggregate size fractions by wet sieving. Macroaggregates were further fractionated to isolate the microaggregates-within-macroaggregates; all soils and fractions were analyzed for SOC and N. The addition of ORs increased soil aggregation and whole SOC and soil N compared to the control and sole N fertilizer treatments. There were no differences among different OR qualities for whole SOC or soil N, but maize alone resulted in greater mean weight diameter (MWD), macroaggregate SOC and N than sole added Calliandra. The addition of N fertilizer only influenced SOC and soil N dynamics in combination with maize where SOC, soil N and aggregation were lower with the addition of N fertilizer, indicating an increased decomposition and loss of SOC and soil N due to a faster aggregate turnover after addition of N fertilizer. In conclusion, compared to high quality ORs, low quality ORs result in greater aggregate stability and a short-term accumulation of macroaggregate SOC and N. However, the addition of N fertilizers negates these effects of low quality ORs.